Hubungan Kepemimpinan Klinis Perawat dengan Penerapan Budaya Patient Safety - Eliati, Eliati; Susanti, Devi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the relationship between the clinical leadership of nurses and the implementation of patient safety culture at the H. Sahudin Kutacane Regional Hospital. The method used is descriptive-analytical correlational research with a cross-sectional study approach. The results of the research show that the characteristics of the respondents at H. Sahudin Kutacane Regional Hospital, the majority of respondents were aged 30 - 39 years, the majority of respondents were female, almost all of the respondents had a D-III level of education in Nursing and the majority of respondents had 6 - 10 years of service. years and there is a significant relationship between clinical leadership of nurses and the implementation of patient safety culture with a p-value of 0.015. In conclusion, clinical leadership possessed by nurses is related to the implementation of patient safety culture in hospitals. Keywords: Culture, Clinical Leadership, Patient Safety.